2010
DOI: 10.4049/jimmunol.0903940
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Mechanisms of IL-2–Dependent Maintenance of Functional Regulatory T Cells

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
164
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(177 citation statements)
references
References 24 publications
11
164
2
Order By: Relevance
“…These data, together with earlier studies suggesting that vitamin D increases Foxp3 expression in human naïve T-cell cultures [10,28], indicate that vitamin D acts through several different mechanisms to enhance Foxp3 expression. IL-2 plays a central role in the maintenance of a functional Treg cell compartment [29,30]. Interestingly, our data suggest that one mechanism by which 1α25VitD3 may act to maintain Treg cells is via the observed increased expression of the alpha chain of the IL-2 receptor, CD25, and this could be relevant to all of the pathways proposed above.…”
mentioning
confidence: 69%
“…These data, together with earlier studies suggesting that vitamin D increases Foxp3 expression in human naïve T-cell cultures [10,28], indicate that vitamin D acts through several different mechanisms to enhance Foxp3 expression. IL-2 plays a central role in the maintenance of a functional Treg cell compartment [29,30]. Interestingly, our data suggest that one mechanism by which 1α25VitD3 may act to maintain Treg cells is via the observed increased expression of the alpha chain of the IL-2 receptor, CD25, and this could be relevant to all of the pathways proposed above.…”
mentioning
confidence: 69%
“…Several studies have focused on two sets of signals-interleukin-2 (IL-2) and antigen itself [60,61]. Thus, IL-2 is required for the survival of Treg and for maintaining their functional activity by promoting expression of FOXP3 and mediators of suppression, particularly CTLA-4 [62]. Answers to environmental antigens may provide enough IL-2 to maintain a Treg cell repertoire in healthy individuals.…”
Section: Treg Functionsmentioning
confidence: 99%
“…Cytokines-IL-2 foremost-are thought to be the main controllers of Treg proportions and numbers (15)(16)(17)(18)(19)(20)(21)(22), although the relative importance of these controllers varies with location and subphenotype [e.g., the alarmin IL-33 has a more profound role in tissue Tregs (21)(22)(23)]. Perhaps surprisingly, in light of this apparently tight control, there is a wide range of variation in Treg proportions, with several studies having observed up to fourfold variation in the blood of healthy humans (e.g., refs.…”
mentioning
confidence: 99%